Research Mapping on Fintech in Southeast Asia: Bibliometric Analysis and VOSviewer Visualization - Judijanto, Loso; Jauhari, Burhanuddin; Nampira , Ardi Azhar (Westscience Press, 2025)
This study explores the evolving landscape of Fintech research in Southeast Asia through a comprehensive bibliometric analysis using data from the Scopus database and visualized via VOSviewer. The analysis identifies key research themes, influential authors, collaborative networks, and temporal trends shaping the field. Results reveal five major thematic clusters: financial inclusion and digital transformation; machine learning and data-driven finance; blockchain and decentralized systems; risk and decision-making; and systemic development and regulation. The keyword overlay and heatmap visualizations indicate a temporal shift from technology-centered studies to more inclusive, impact-oriented research, particularly after 2021. Co-authorship and country collaboration networks highlight the dominance of China, India, and the United States, while Southeast Asia demonstrates growing but uneven scholarly engagement. This study contributes to a deeper understanding of the intellectual structure of Fintech research in the region and provides a strategic foundation for future academic inquiry, policy development, and digital financial innovation.